THE ROLE OF SELF-CARE PRACTICES IN MENTAL HEALTH AND WELL-BEING: A COMPREHENSIVE REVIEW - Tushe, Mirela (International Journal of NeuroOncology and Therapeutics, 2025)
This paper investigates the significant role of self-care practices in promoting mental health and enhancing overall well-being. While many individuals turn to short-term fixes like caffeine and sleep to recover from stress, self-care goes beyond recovery and encompasses holistic practices that nurture the body and mind. By examining relevant scientific literature, this study explores how different self-care activities such as mindfulness, physical activity, nature exposure, and social connection influence mental health outcomes like anxiety, depression, and stress. The paper aims to clarify the distinction between recovery and self-care and emphasize the importance of making self-care an integral part of daily life.